Pulmonary Computed Tomography Parenchymal and Vascular Features Diagnostic of Postablation Pulmonary Vein Stenosis. Issue 3 (May 2020) - Goitein, Orly; Konen, Eli; Lieberman, Sivan; Marom, Edith M.; Brodov, Yafim; Bekker, Elena; Beinart, Roy; Di Segni, Elio; Glikson, Michael; Davidson, Tima
Abstract : Purpose: The purpose of this study was to define the full spectrum of pulmonary computed tomography (CT) changes characteristic of postablation pulmonary vein stenosis (PVS). Materials and Methods: We retrospectively reviewed our pulmonary vein isolation database. PVS was graded as follows: grade 1:<50%, grade 2: 50% to 75%, grade 3: 76% to 99%, and grade 4: total occlusion. CT parenchymal and vascular changes were detected and correlated with clinical course and nuclear scans. Results: Of 486 patients who underwent pulmonary vein isolation, 56 patients (11%) were symptomatic, prompting referral to CT evaluation. Grades 1, 2, 3, and 4 PVS were documented in 42, 1, 2, and 11 patients, respectively. Apart from PVS, abnormal CT findings were present only in patients with PVS grades 2 to 4. Pulmonary parenchymal changes (consolidation, "ground glass" opacities, interlobular septal thickening, and volume loss) were found in PVS grades 2 to 4. Pulmonary vascular changes (oligemia, "sluggish flow, " and collateral mediastinal vessels) were shown in patients with grades 3 to 4 PVS. Concomitant nuclear scans documented reduced lung perfusion. All findings were located to the lobe drained by the affected vein. Complete resolution of pulmonary findings on follow-up CT scans was demonstrated in 20% of patients. Eleven stents were inserted in 7 patients with PVS grades 2 to 4, none of which demonstrated radiologic or clinical resolution. Conclusions: A typical CT complex of both parenchymal and vascular findings in the affected lobe is diagnostic of postablation PVS. Lack of clinical and radiologic resolution in most patients, even after stent insertion, further highlights the importance of early recognition of this underdiagnosed condition.